BPC transcription factors and a Polycomb Group protein confine the expression of the ovule identity gene SEEDSTICK in Arabidopsis. (4th February 2020) - Petrella, Rosanna; Caselli, Francesca; Roig‐Villanova, Irma; Vignati, Valentina; Chiara, Matteo; Ezquer, Ignacio; Tadini, Luca; Kater, Martin M.; Gregis, Veronica
Summary: The BASIC PENTACYSTEINE (BPC) GAGA (C‐box) binding proteins belong to a small plant transcription factor family. We previously reported that class I BPCs bind directly to C‐boxes in the SEEDSTICK ( STK ) promoter and the mutagenesis of these cis ‐elements affects STK expression in the flower. The MADS‐domain factor SHORT VEGETATIVE PHASE (SVP) is another key regulator of STK . Direct binding of SVP to CArG‐boxes in the STK promoter are required to repress its expression during the first stages of flower development. Here we show that class II BPCs directly interact with SVP and that MADS‐domain binding sites in the STK promoter region are important for the correct spatial and temporal expression of this homeotic gene. Furthermore, we show that class I and class II BPCs act redundantly to repress STK expression in the flower, most likely by recruiting TERMINAL FLOWER 2/LIKE HETEROCHROMATIN PROTEIN 1 (TFL2/LHP1) and mediating the establishment and the maintenance of H3K27me3 repressive marks on DNA. We investigate the role of LHP1 in the regulation of STK expression. In addition to providing a better understanding of the role of BPC transcription factors in the regulation of S TK expression, our results suggest the existence of a more general regulatory complex composed of BPCs, MADS‐domain factors and Polycomb Repressive Complexes that co‐operate to regulate gene expression in reproductive tissues. We believe that our data along with the molecular model described here could provide significant insights for a more comprehensive understanding of gene regulation in plants. Significance Statement: Both class I and class II BASIC PENTACYSTEINE (BPC) proteins regulate the homeotic gene SEEDSTICK ( STK ) together with the MADS‐domain factor SHORT VEGETATIVE PHASE (SVP); furthermore, the component of PRC1 complex LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) is involved in STK repression modulating H3K27me3 deposition and maintenance on the locus.